Pantangan Ibu Hamil dalam Adat Dayak : Antara Mitos dan Kesehatan Reproduksi - Fitriani Ningsih; Witri Winda Sari; Yista Yista; Yola Selvia; Yurischa Yurischa; Yunni Wulandari (Pusat riset dan Inovasi Nasional, 2025)
In the Dayak indigenous community, pregnancy taboos are part of local wisdom passed down from generation to generation. These taboos are often regarded as myths, but some have rational foundations from the perspective of reproductive health. This study aims to identify the types of pregnancy taboos in Dayak culture, evaluate the underlying reasons, and assess their relevance from the standpoint of modern health. The research was conducted using qualitative methods through literature review and content analysis of related scientific journals. The results indicate that some taboos correlate with principles of nutrition, fetal safety, and stress control in pregnant women.